Implementation of SAK EMKM in CV Adro Textile through an Action Research Approach as a Form Financial Management Accountability - Ali Farhan; Resha Dwi A. P. Mulyono (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2019)
Most of micro business industries have a problem on accountabilty and lack of information on financial and management knowledges. CV Adro Textile is one of the micro business which faced those problems. This research aims to introduce an accounting policy and standard into action research methodolgy for a micro business such as CV Adro Textile. CV Adro textile is a manufacturing company that engaged in the garment sector. During its business, CV Adro Textile faced some problems regarding to the financial information. CV Adro Textile cannot ensure the profit that been generated, the cash turnover, and the production cost as well as the financial information for the taxation need. Through the action research, this research tried to implement the EMKM financial accounting standard to fulfill CV Adro Textile’s needs to the accountable financial statements. Action research is a research procedure aims to implement a new policy based on needs and problems of the research object. The results of this research were an accounting recording system for CV Adro Textile based on SAK EMKM and an evaluation of the SAK EMKM application that apparently could not accommodate the whole recording needs and information of an industry. This paper contribute to the way of intorducing an accounting standart into a micro entity